Associations Between Ethnicity and Admission to Intensive Care Among Women Giving Birth: A Cohort Study. Issue 1 (22nd March 2023) - Jardine, J.; Gurol-Urganci, I.; Harris, T.; Hawdon, J.; Pasupathy, D.; van der Meulen, J.; Walker, K.; ,
Abstract : ( BJOG . 2022;129:733–742) Intensive care unit (ICU) admission among women giving birth is an indicator of severe maternal morbidity and is associated with a high risk of mortality. Studies in the United Kingdom have shown that patients from ethnic minority groups have worse maternal outcomes compared with White patients. Previous studies in the Netherlands, Canada, and the United States have shown an ethnic disparity in maternal ICU admissions. This study by Jardine et al aimed to determine the association between ethnicity and ICU admission among patients giving birth in the United Kingdom and Wales.